Breaking barriers: The potential of nanosystems in antituberculosis therapy - Carnero Canales, Christian S.; Marquez Cazorla, Jessica Ingrid; Marquez Cazorla, Renzo Marianito; Roque-Borda, Cesar Augusto [UNESP]; Polinário, Giulia [UNESP]; Figueroa Banda, Rufo A.; Sábio, Rafael Miguel [UNESP]; Chorilli, Marlus [UNESP]; Santos, Hélder A.; Pavan, Fernando Rogério [UNESP] (Elsevier, 2024)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, continues to pose a significant threat to global health. The resilience of TB is amplified by a myriad of physical, biological, and biopharmaceutical barriers that challenge conventional therapeutic approaches. This review navigates the intricate landscape of TB treatment, from the stealth of latent infections and the strength of granuloma formations to the daunting specters of drug resistance and altered gene expression. Amidst these challenges, traditional therapies often fail, contending with inconsistent bioavailability, prolonged treatment regimens, and socioeconomic burdens. Nanoscale Drug Delivery Systems (NDDSs) emerge as a promising beacon, ready to overcome these barriers, offering better drug targeting and improved patient adherence. Through a critical approach, we evaluate a spectrum of nanosystems and their efficacy against MTB both in vitro and in vivo. This review advocates for the intensification of research in NDDSs, heralding their potential to reshape the contours of global TB treatment strategies.
Keywords: Barriers; Drug resistance; Mycobacterium tuberculosis; Nanoscale drug delivery systems; Tuberculosis